A Productive Clash of Cultures: Injecting Economics into Leadership Research - Christian Zehnder; Holger Herz; Jean-Philippe Bonardi (Center for Economic Studies and ifo Institute (CESifo), 2016)
Research on leadership in economics has developed in parallel to the literature in management and psychology and links between the fields have been sparse. Whereas modern leadership scholars mostly focus on transformational and related leadership styles, economists have mainly emphasized the role of contracts, control rights, and incentives. We argue that both fields could profit from enriching their approach with insights from the other field. We review and synthesize the economics literature on leadership in organizations and discuss how leadership scholars in management and psychology can benefit from the detailed understanding of transactional methods that economists have developed. We link the contributions in economics to a broad set of topics including the foundations of leadership, leader emergence, and leader effectiveness. At the same time, we also point out limitations of the economic approach and outline how the integration of leadership research and economics would broaden the scope of future studies.
Keywords: 330; leadership; economics; foundations; emergence; effectiveness